Autoimmune liver damage in patients with primary Sjogren's syndrome associated with anticentromeric antibodies - B. D. Chalcev; V. I. Vasiliev; S. G. Palshina; A. V. Torgashina; E. V. Sokol; J. I. Khvan; E. B. Rodionova; T. N. Safonova; T. P. Nekrasova (Современная ревматология, 2021)
Objective: to determine the frequency, spectrum and severity of liver affection in anti-centromere antibodies (ACA) positive patients with primary Sjogren's syndrome (pSS).Patients and methods. 119 ACA-positive patients with pSS were included in the study, 37 (31%) of them had signs of liver damage, 3 of these patients were excluded from the study (2 had cholelithiasis, 1 had viral hepatitis B). Signs of autoimmune liver damage were found in 34 (28.6%) patients, most of them were seropositive for antimitochondrial antibodies (AMA). The diagnosis of primary biliary cholangitis (PBC) and autoimmune hepatitis (AIH) was established according to the recommendations of the American Association for the Study of Liver Diseases, the Russian Gastroenterological Association and the Russian Society for the Study of the Liver. In 5 (14.7%) patients the cause of cholestasis remained unspecified.Results and discussion. AMA were found in 73.5% of patients, elevated serum IgM levels – in 57.6%. Clinically liver damage in most cases was characterized by an asymptomatic, slowly progressive course without a dramatic increase of symptoms over time. Liver cirrhosis was found in 14.7% of patients. According to clinical, laboratory and morphological manifestations, PBC was diagnosed in 21 patients, 4 of them also had a cross syndrome with AIH. AMA-negative PBC was found in 3 patients and isolated AIH – in 1. In most cases, histological stage I of PBC was detected. During follow-up, median of 7 years (range from 2 to 15 years), in 7 patients with stage I PBC and in 7 AMA-positive patients without functional liver disorders no clinical, laboratory or instrumental progression of liver damage was noted. In this regard, it was suggested that these patients have epitheliitis of the biliary ducts as manifestation of glandular affection in pSS, and not true PBC.Conclusion. Autoimmune liver lesions are detected in 28.6% of ACA-positive patients with pSS, most (41.2%) of them develop epitheliitis of the biliary ducts as pSS manifestation or a combination of pSS with PBC (with the same frequency), less often PBC / AIH cross syndrome is diagnosed. PBC / pSS-related epitheliitis of the biliary ducts in ACA-positive patients is characterized by a slowly progressive asymptomatic course in most cases and rarely leads to the development of liver cirrhosis.